Reconnoitering Education Literacy and Equality: Bibliometrics Analysis of the term “Education Literacy and Equality” - Elihami, Elihami; Sua, Andi Tenri; Mahyuddin, Muhammad Junaedi (Journal of Nonformal Education, 2021)
The proposition of nonformal education were to characterize the education literacy and equality through bibliometric analysis. The research aimed to assess education literacy and equality research output through the period of 2020- 2021.The Scopus and google scholar database has used to retrieve records related to education literacy and equality. The VOSviewer application is used to analyze the retrieved bibliographic citation data. The literacy and equality research publication are analyzed and interpreted using the retrieved data. The performance of the most productive countries, authors, journals, languages, institutions, keywords, and citation references is examined. The rate of relative growth and the time required to double have been calculated. The performance of the most productive countries and the greatest number of articles are published in the form of 470 total articles. In the years 2020-2021, the maximum number of papers published is 470. The research novelty showed that there was the addition of new literature about the education literacy and equality through bibliometric analysis and there were variation in source between Scopus and Google Scholar database.